Optimasi Sistem Distribusi melalui Penempatan Express Feeder Menggunakan Algoritma Genetika untuk Mengurangi Rugi Daya - Syauqil Aman, Rizaldi; Priatna, Edvin; Risnandar, Muhammad Aris (Fakultas Teknik Universitas Garut, 2025)
Power losses in distribution systems are one of the main problems affecting the efficiency of electricity distribution. This study aims to minimize power losses through the installation of express feeders and new load break switches (LBS). The optimization method used to determine the optimal location for installation is the Genetic Algorithm. The Genetic Algorithm and power flow calculations were implemented using MATLAB 2024a software, followed by a validation process comparing the power flow results from MATLAB 2024a with simulation results from ETAP 19.0.1 software. The case study was applied to the CLDG distribution system, comparing the existing conditions with the conditions after optimization. The simulation results for the existing conditions showed a total power loss of 554.109 kW. After applying optimization using the genetic algorithm method to determine the optimal locations for the express feeder and new LBS, power losses were successfully minimized to 308.4 kW. These results demonstrate that installing the express feeder and new LBS using the genetic algorithm method is an effective solution for minimizing power losses in the distribution system.